Asy-Syuhada Grand Mosque in Pamekasan as a Center for Digital-Based Scientific Development for Urban Communities - Mubarok, A. Khuzainol; Sa’diyah, Halimatus; Mutammimah, Darun; Kamilia, Dina; Khoiroh, Anisya Umi (Permata : Jurnal Pendidikan Agama Islam, 2026)
This study is motivated by the digital transformation phenomenon carried out by the Great Mosque of Asy-Syuhada’ Pamekasan in developing its educational and da’wah functions. The use of digital media such as YouTube, Radio 88.6 FM, and social media has created new opportunities for urban communities to remain connected to religious activities amid busy modern life. This research aims to reveal how the Asy-Syuhada’ Mosque develops Islamic education through digital media and how the community responds to this innovation. A descriptive qualitative method was employed, with data collected through interviews, observations, and documentation. The results show that the mosque’s digital learning activities are well-organized and participatory, involving administrators, lecturers, youth organizations, and congregants. Digital media play an essential role in expanding the scope of da’wah, strengthening religious literacy, and fostering a sense of belonging among the congregation. Therefore, the mosque’s digitalization can be regarded as a form of socio-religious innovation that maintains spiritual continuity while reinforcing the mosque’s role as a modern Islamic learning center in the digital era.